2015
DOI: 10.1111/jpi.12217
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin‐mediated Bim up‐regulation and cyclooxygenase‐2 (COX‐2) down‐regulation enhances tunicamycin‐induced apoptosis in MDAMB‐231 cells

Abstract: Melatonin is involved in many physiological functions, and it has differential effects on apoptosis in normal and cancer cells. However, the mechanism of its antitumor roles is not well understood. In this study, we show that melatonin enhances tunicamycin-induced apoptosis in human breast carcinoma MDA-MB-231 cells. Melatonin up-regulates pro-apoptotic protein Bim expression at the transcriptional levels in the presence of tunicamycin. Melatonin inhibits tunicamycin-induced COX-2 expression in MDA-MB-231 cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 52 publications
3
27
0
Order By: Relevance
“…The disruption of nocturnal rise in melatonin production and secretion due to excessive light exposure during the normal dark period, i.e., light pollution, has long been known to correlate with a higher cancer risk [175,176,177,178,179,180]. Any alteration in the nocturnal rise in circulating melatonin, however, is unavoidably also accompanied by a general perturbation of circadian rhythms, which are a result of malfunction of the activity of the master biological clock, the suprachiasmatic nucleus (SCN).…”
Section: Melatonin and Cancer Progressionmentioning
confidence: 99%
“…The disruption of nocturnal rise in melatonin production and secretion due to excessive light exposure during the normal dark period, i.e., light pollution, has long been known to correlate with a higher cancer risk [175,176,177,178,179,180]. Any alteration in the nocturnal rise in circulating melatonin, however, is unavoidably also accompanied by a general perturbation of circadian rhythms, which are a result of malfunction of the activity of the master biological clock, the suprachiasmatic nucleus (SCN).…”
Section: Melatonin and Cancer Progressionmentioning
confidence: 99%
“…Melatonin exerts anti-apoptotic effects in normal cells exposed to toxic agents or metabolic injury. However, melatonin usually has the opposite effect on cancer cells and induces apoptosis in a wide range of different tumors (e.g., breast, prostate, cervix, liver, colon, pancreas, kidney, neuro) [18, 20, 24, 25, 28, 7578]; thus, the induction of apoptosis of cancer cells (but not of normal cells) is one of the mechanisms by which melatonin limits tumor growth [61, 7988]. This specifically relates to lung cancer given that melatonin treatment dose- and time- dependent decreased the viability of human A549 and PC9 lung adenocarcinoma cells, and increased their apoptotic index.…”
Section: Effect Of Melatonin On Nsclc Cell Apoptosismentioning
confidence: 99%
“…Melatonin upregulates FOXO3a-mediated activation of the proapoptotic protein Bim and enhances endoplasmic reticulum stressinduced apoptosis through inhibition of COX-2 expression and reduction of Bcl-2 levels, and by an elevation of the pro-apoptotic transcription factor C/EBP homologous protein (CHOP). Woo et al demonstrated that melatonin has an antitumor function through down-regulation of COX-2 expression by inhibition of NF-κB and p38 MAPK activation [62]. Therefore, the stimulatory effects of melatonin on apoptosis in cancer cells involve both the intrinsic and the extrinsic apoptotic pathways [6].…”
Section: Activation Of Intrinsic and Extrinsic Apoptotic Pathwaysmentioning
confidence: 99%